Non-structure protein ORF1ab (NSP8) in SARS-CoV-2 contains potential γδT cell epitopes - Du, Boyu; Guo, Yang; Li, Gang; Zhu, Yunhe; Wang, Yunfu; Xi, Xueyan (Frontiers in Microbiology, 2022)
Upon activation by the pathogen through T-cell receptors (TCRs), γδT cells suppress the pathogenic replication, thus play important roles against viral infections. Targeting SARS-CoV-2 via γδT cells provides alternative therapeutic strategies. However, little is known about the recognition of SARS-CoV-2 antigens by γδT cells. We discovered a specific Vγ9/δ2 CDR3 from analyzing γδT cells derived from the patients infected by SARS-Cov-2. Using a cell model exogenously expressing γδ-TCR established, we further screened the structural motifs within the CDR3 responsible for binding to γδ-TCR. Importantly, these sequences were mapped to NSP8, a non-structural protein in SARS-CoV-2. Our results suggest that NSP8 mediates the recognition by γδT cells, thus could serve as a potential target for vaccines.